Multicomponent Lattice Boltzmann Simulations of Gas Transport in a Coal Reservoir with Dynamic Adsorption - Zhigao Peng; Shenggui Liu; Songlei Tang; Yuechao Zhao; Yingjun Li (Geofluids)
Gas adsorption occurs when the dynamic adsorption equilibrium conditions of the local adsorptive sites are broken. In the overall process of unconventional natural gas generation, enrichment, storage, and production, this phenomenon plays a significant role. A double-distribution Lattice Boltzmann model for solving the coupled generalized Navier-Stokes equation and advection-diffusion equation with respect to the gas-solid dynamic adsorption process is proposed for multicomponent gas migration in the unconventional reservoir. The effective diffusion coefficient is introduced to the model of gas transport in the porous media. The Langmuir adsorption rate equation is employed to control the adsorption kinetic process of gas-solid adsorption/desorption. The model is validated in two steps through fluid flow without and with gas diffusion-adsorption between two parallel plates filled with porous media, respectively. Simulation results indicate that with other parameters being equal, the rate of gas diffusion in the porous material and the area of the dynamic adsorption equilibrium-associated region increase with the matrix porosity/permeability. Similar results will happen with a greater saturation adsorption amount or a lower Langmuir pressure. The geometric effect on adsorption is also studied, and it is found that a higher specific surface area or free flow region can enhance the gas transport and the rate of adsorption.